Developing a knowledge achievement test on the laws of football for students of the Faculty of Physical Education and Sports Sciences at the Universities of Sulaimani and Halabja - Mahmoud, L.Dr. Bamo Nabaz (Sulaimani Journal for Humanities, 2025)
The research aimed to develop a legal knowledge achievement test in football for students of the College of Physical Education and Sports Sciences at the Universities of Sulaimani and Halabja. The goal was to identify the students' level of legal knowledge in football. The researcher used a descriptive survey methodology, deemed suitable for the nature of the research. The research population consisted of 185 third-year students from the College of Physical Education and Sports Sciences at the Universities of Sulaimani and Halabja. A sample of 80 students was randomly selected for the test's construction using a systematic sampling method, while 10 students were chosen for a pilot sample. The researcher based the legal knowledge achievement test on the 2024 football law curriculum. One hundred behavioral objectives (recall, comprehension, and application) were defined, comprising 40 questions. A specifications table was used to determine the number and type of questions for the behavioral objectives. The relative importance of the law's provisions was considered by experts and specialists, and the questions focused on recall, comprehension, and application. Multiple-choice questions were used for the answer choices. After confirming the scientific basis of the test, it was administered. A pilot test was conducted, followed by the main application, test correction, and extraction of the ease, difficulty, and discrimination indices. After that, the internal consistency of the items was established by finding the correlation coefficient between the item score and the total score, and between the item score and the total score of the domain to which the item belongs. Standard levels were extracted, and the researcher used the statistical package system as statistical means to reach the research results, including: building and standardizing the legal knowledge achievement test in football for the research sample.
Keywords: Building; Legal Knowledge Test; Football